Digital Transformation of Matrimonial Contracts: A Normative Empirical Evaluation of Virtual Marriage in Islamic Law: (Transformasi Digital Kontrak Perkawinan: Evaluasi Empiris Normatif tentang Perkawinan Virtual dalam Hukum Islam) - Muhammadong (Journal of Islamic Education and Intellectual Discourse (JIED), 2026)
This paper investigates the evolution of the marriage contract (al-aqdu al-nikah) facilitated by digital methods in contemporary society, emphasizing its legitimacy under Islamic law. The swift advancement of communication technology has facilitated the phenomenon of virtual marriage, prompting inquiries over the validity of ijab qabul conducted through online platforms. This occurrence necessitates an exhaustive legal examination rooted in Islamic jurisprudence. The aim of this study is to examine the permissibility and legal standing of virtual marriage contracts within an Islamic legal framework. This study utilizes a qualitative research methodology through a normative juridical lens, drawing on primary sources including the Qur’an, Hadith, and classical fiqh literature, alongside contemporary scholarly perspectives. The results demonstrate that the legitimacy of a digital marriage contract is contingent upon the satisfaction of fundamental pillars (rukun) and conditions (syarat) of marriage, including the presence of the bride and groom, witnesses, consent, and the clarity of ijab qabul, even when executed via digital medium. Nevertheless, scholarly disagreements endure, especially about matters of physical presence and the associated hazards of deception. under conclusion, virtual marriage may be deemed valid under Islamic law under specific conditions, contingent upon the fulfillment of all essential prerequisites and the establishment of legal protections.